The SHORT-ROOT-like gene PtSHR2B is involved in Populus phellogen activity - Miguel, Andreia; Milhinhos, Ana; Novák, Ondřej; Jones, Brian; Miguel, Célia M (Journal of Experimental Botany, 2016)
SHORT-ROOT (SHR) is a GRAS transcription factor first characterized for its role in the specification of the stem cell niche and radial patterning in Arabidopsis thaliana (At) roots. Three SHR-like genes have been identified in Populus trichocarpa (Pt). PtSHR1 shares high similarity with AtSHR over the entire length of the coding sequence. The two other Populus SHR-like genes, PtSHR2A and PtSHR2B, are shorter in their 5' ends when compared with AtSHR. Unlike PtSHR1, that is expressed throughout the cambial zone of greenhouse-grown Populus trees, PtSHR2Bprom:uidA expression was detected in the phellogen. Additionally, PtSHR1 and PtSHR2B expression patterns markedly differ in the shoot apex and roots of in vitro plants. Transgenic hybrid aspen expressing PtSHR2B under the 35S constitutive promoter showed overall reduced tree growth while the proportion of bark increased relative to the wood. Reverse transcription-quantitative PCR (RT-qPCR) revealed increased transcript levels of cytokinin metabolism and response-related genes in the transgenic plants consistent with an increase of total cytokinin levels. This was confirmed by cytokinin quantification by LC-MS/MS. Our results indicate that PtSHR2B appears to function in the phellogen and therefore in the regulation of phellem and periderm formation, possibly acting through modulation of cytokinin homeostasis. Furthermore, this work points to a functional diversification of SHR after the divergence of the Populus and Arabidopsis lineages. This finding may contribute to selection and breeding strategies of cork oak in which, unlike Populus, the phellogen is active throughout the entire tree lifespan, being at the basis of a highly profitable cork industry.
Keywords: Cytokinins; kambium; Cambium; Trees; Promoter Regions, Genetic; Hybridization, Genetic; dřevo; Wood; geneticky modifikované rostliny; stromy; Phenotype; hybridizace genetická; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; rostlinné geny; Genes, Plant; Plants, Genetically Modified; rostlinné proteiny; fenotyp; Plant Proteins; Populus; Plant Stems; promotorové oblasti (genetika); stonky rostlin; cytokininy